2008
DOI: 10.1016/j.yhbeh.2007.09.012
|View full text |Cite
|
Sign up to set email alerts
|

An alternate pathway for androgen regulation of brain function: Activation of estrogen receptor beta by the metabolite of dihydrotestosterone, 5α-androstane-3β,17β-diol

Abstract: The complexity of gonadal steroid hormone actions is reflected in their broad and diverse effects on a host of integrated systems including reproductive physiology, sexual behavior, stress responses, immune function, cognition, and neural protection. Understanding the specific contributions of androgens and estrogens in neurons that mediate these important biological processes is central to the study of neuroendocrinology. Of particular interest in recent years has been the biological role of androgen metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 132 publications
3
122
1
1
Order By: Relevance
“…A similar variety of receptor-mediated mechanisms has been shown for T and its 5α-reduced metabolites; whereas 5α-DHT and T activate androgen receptors (AR), 3α-diol and 3β-diol act as a positive allosteric modulator of GABA-A receptor and an ERβ agonist, respectively [28,43]. Although several authors posited the involvement of membrane-bound receptors to account for several rapid actions of T, the molecular identity of these targets remains currently elusive [44].…”
Section: Functions Of 5α-rs In the Central Nervous Systemmentioning
confidence: 67%
“…A similar variety of receptor-mediated mechanisms has been shown for T and its 5α-reduced metabolites; whereas 5α-DHT and T activate androgen receptors (AR), 3α-diol and 3β-diol act as a positive allosteric modulator of GABA-A receptor and an ERβ agonist, respectively [28,43]. Although several authors posited the involvement of membrane-bound receptors to account for several rapid actions of T, the molecular identity of these targets remains currently elusive [44].…”
Section: Functions Of 5α-rs In the Central Nervous Systemmentioning
confidence: 67%
“…The testosterone metabolite, 3α-androstanediol, may have actions via ERβ [78]. Indeed, we have demonstrated that the performance enhancing effects of 3α-diol are attenuated with co-administration of AS-ODNs that are targeted against ERβ, but not ERα, when administered to the hippocampus [74].…”
Section: Erβ-mediated Actions In the Hippocampus For E 2 'S Functionamentioning
confidence: 85%
“…In contrast, in vitro studies suggest that some aspects of androgen protection, including regulation of A␤ generation via APP proteolysis, may be mediated indirectly after aromatization to estradiol . Recent work, suggesting that a metabolite of DHT, 5␣-androstane-3␤,17␤-diol, is active at ER␤, not ER␣ or AR (Lund et al, 2006;Pak et al, 2007;Handa et al, 2008), could also suggest that AR and/or ER␤, but not ER␣, mediate the effects of DHT on A␤ levels in males. Further work will clearly be important to understand to what degree the direct application of hormones to cultured neurons, which are capable of producing their own steroids in vitro (Prange-Kiel and Rune, 2006), reflects the effects of systemic hormones in vivo.…”
Section: B Preclinical Studiesmentioning
confidence: 99%